2019
DOI: 10.3389/fmicb.2019.00782
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Organic Acid Production and In Vivo Food Pathogen Suppression by Probiotic S. thermophilus and L. bulgaricus

Abstract: Foodborne pathogens are a major source of morbidity and mortality worldwide. For this cause, exploring various effective ways of suppressing their spread is at the forefront of many research projects. The current study aims to investigate the in vitro organic acid production of S. thermophilus KLDS 3.1003 and L. bulgaricus KLDS 1.0207 strains, their in vivo suppression of and immuno-modulatory effects against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Earlier, Bian et al (2015) showed that antimicrobial substances produced by L. helveticus KLDS 1.8701 could inhibit a range of foodborne pathogens, especially L. monocytogenes ATCC119115. Also, L. bulgaricus KLDS 1.0207 can produce sufficient pathogen-inhibiting organic acid (lactic and acetic acids) in vitro, and this increased with carbon source supplementation (Evivie et al, 2019). Our recent report and findings from the current study strongly suggest that the inhibitory properties exhibited by this strain can be attributed to acid metabolites.…”
Section: Antimicrobial Activitysupporting
confidence: 62%
See 1 more Smart Citation
“…Earlier, Bian et al (2015) showed that antimicrobial substances produced by L. helveticus KLDS 1.8701 could inhibit a range of foodborne pathogens, especially L. monocytogenes ATCC119115. Also, L. bulgaricus KLDS 1.0207 can produce sufficient pathogen-inhibiting organic acid (lactic and acetic acids) in vitro, and this increased with carbon source supplementation (Evivie et al, 2019). Our recent report and findings from the current study strongly suggest that the inhibitory properties exhibited by this strain can be attributed to acid metabolites.…”
Section: Antimicrobial Activitysupporting
confidence: 62%
“…bulgaricus KLDS 1.0207, isolated from traditional dairy products from Sinkiang Province, China, has shown promising attributes recently in alleviating lead (Pb) toxicity in vivo in both prevention and treatment groups (Li et al, 2017). Besides, it can produce high amounts of pathogen-suppressing organic acid in vitro, improve immunity functions, and prevent organ damage in vivo (Evivie et al, 2019). However, nothing is known about its antimicrobial anti-inflammatory and tolerance properties (in vitro).…”
Section: Introductionmentioning
confidence: 99%
“…High lactate production is a hallmark of this species. Of the two species most frequently used as starters in commercial yogurt making, L. delbrueckii produces greater amounts of lactate than S. thermophilus [47]. Production of both lactic and acetic acids as seen here, can act synergistically to produce low pH [48].…”
Section: Discussionmentioning
confidence: 69%
“…These methods may help provide ideas for improving heterologous protein expression in S. thermophilus. Nevertheless, S. thermophilus as a traditional starter for yogurt is a potential probiotic (Evivie et al, 2019). It not only has remarkable fermentation characteristics but also plays a positive role in maintaining intestinal health (Vitetta et al, 2019).…”
Section: Discussionmentioning
confidence: 99%